IMPLEMENTASI METODE SAVI UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA MOJOAGUNG JOMBANG - Muhsin, Ali (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2020)
Quality learning processes involve many things, one of which is the method or model applied by the teacher. If a teacher conveys varied and stimulating learning, students will be more interested in listening to the material presented. Conversely, if the teacher only teaches with conventional methods, namely lectures, students will be bored and not interested in listening to the material being taught. In this case the role of the learning method is very important to increase students' learning motivation, especially in the XI IPA class students.Assulaimaniyah whose application of learning is still a conventional method. They need varied learning not monotonous in order to support maximum learning outcomes, as well as the Application of SAVI Learning Methods to Increase Learning Motivation Sisawa Class XI Science MA.Assulaimaniyah Mojoagung Jombang. Based on this background, this study aims to conduct and determine the application of SAVI learning methods to improve student learning motivation when applied in the XI IPA MA class. Assulaimaniyah. Type of qualitative research with methods of collecting data on observation, interviews, documentation and library data. Data Analysis Techniques Data collection as well as data reduction, data presentation, verification and conclusions. The results showed that when the application of the SAVI method was applied, students who were previously lacking in enthusiasm in receiving learning were more enthusiastic and active in participating in these varied learning methods, so students could learn more optimally in learning. Supporting factors, positive support and encouragement from homeroom teacher and researcher motivation. Inhibiting factors Factors of oneself, such as lack of enthusiasm and enthusiasm that arise from them selves.